Electricity storage element and electricity storage device

By using amorphous carbon in the negative active material layer of the lithium-ion secondary battery and optimizing its potential range, the problems of insufficient initial capacity and increased hysteresis of the battery are solved, and high initial capacity and good charge and discharge control are achieved.

CN111328434BActive Publication Date: 2025-03-14GS YUASA INT LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201880072716.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-11-22
Filing Date
2018-11-21
Publication Date
2025-03-14
Estimated Expiration
2038-11-21

AI Technical Summary

Technical Problem

When the initial capacity of the existing lithium-ion secondary batteries is not too large, the voltage curves during charging and discharge are prone to deviate significantly, resulting in an increase in hysteresis and making it difficult to perform charging and discharge control.

Method used

Amorphous carbon is used as the active substance in the negative electrode active substance layer, and the change ratio of the discharge capacity and potential of the negative electrode is optimized so that it has more than one peak value within a range of 0.8V or more and 1.5V or less, and the negative electrode potential when fully charged is set to 0.25V or more.

Benefits of technology

While having a relatively high initial capacity, it is possible to suppress the increase in hysteresis during charging and discharge, and improve the ease of charging and discharging control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111328434B_ABST
    Figure CN111328434B_ABST
Patent Text Reader

Abstract

The present invention provides a storage element and a storage device that suppress the increase of hysteresis during charging and discharging while having a relatively high initial capacity. In this embodiment, the storage element has a negative electrode, the negative electrode has a negative electrode active material layer containing amorphous carbon as an active material, based on the result of measuring the potential (V) of amorphous carbon relative to the discharge quantity (Q) of the amorphous carbon, the change ratio (dQ / dV) of the potential (V) per unit amount of discharge quantity (Q) is calculated, and a curve representing the change ratio (dQ / dV) relative to the potential (V) has one or more peaks in the range of the potential of the amorphous carbon being 0.8V or more and 1.5V or less, and the potential of the negative electrode when fully charged is 0.25V or more according to the lithium potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electric storage element such as a lithium ion secondary battery, and an electric storage device including a plurality of such electric storage elements. Background Art

[0002] Conventionally, there is known a lithium ion secondary battery including an electrode winding group in which a positive electrode, a negative electrode, and a separator are wound, and an electrolyte solution in a battery container.

[0003] The battery described in Patent Document 1 discloses the following technical contents. The positive electrode has a current collector and a positive electrode mixture coated on both sides of the current collector, and the positive electrode mixture contains a layered lithium-nickel-manganese-cobalt composite oxide as a positive electrode active material. The coating amount of the positive electrode mixture on one side is 110 to 170 g / m 2 The density of the positive electrode mixture is 2.5-2.8 g / cm 3 The negative electrode comprises a current collector and a negative electrode mixture coated on both sides of the current collector, wherein the negative electrode mixture comprises amorphous carbon as a negative electrode active material. The electrolyte comprises cyclic carbonate, chain carbonate, cyclic sulfonate and vinylene carbonate as a non-aqueous solvent.

[0004] Prior Art Literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-091927 Summary of the invention

[0007] Problems to be solved by the invention

[0008] Although a storage element such as the battery described in Patent Document 1 is designed to have sufficient input and output performance for use in hybrid vehicles, the initial capacity is often not too large. In recent years, the use of storage elements for automobiles has become popular, and therefore, in addition to sufficient input and output characteristics, a storage element having a relatively high initial capacity is required.

[0009] Therefore, research on storage elements using amorphous carbon as an active material that increases the charge and discharge capacity compared to conventional amorphous carbon is considered. However, in such storage elements, the voltage curves during charge and discharge may deviate significantly, that is, the hysteresis increases. If the hysteresis increases, it is difficult to control charge and discharge.

[0010] An object of the present embodiment is to provide an electric storage element having a relatively high initial capacity and suppressing an increase in hysteresis during charging and discharging, and an electric storage device including a plurality of such electric storage elements.

[0011] Means for solving problems

[0012] The storage element of this embodiment includes a negative electrode, which has a negative electrode active material layer containing amorphous carbon as an active material. Based on the result of measuring the potential (V) of the amorphous carbon relative to the discharge quantity (Q) of the amorphous carbon, the change ratio (dQ / dV) of the potential (V) per unit amount of discharge quantity (Q) is calculated, and a curve representing the change ratio (dQ / dV) relative to the potential (V) has one or more peaks in the range of the potential of the amorphous carbon being greater than 0.8V and less than 1.5V, and the potential of the negative electrode when fully charged is greater than 0.25V according to the lithium potential.

[0013] The power storage device of this embodiment includes a plurality of the above-mentioned power storage elements, the plurality of power storage elements are connected in series, and the power storage element has a positive electrode, which contains, as an active material, an α-NaFeO2 structure and a Li 1+x M 1-x A lithium transition metal composite oxide represented by the chemical composition of O2 (wherein M is a transition metal, 0<x<0.3).

[0014] Effects of the Invention

[0015] According to the present embodiment, it is possible to provide an electric storage element having a relatively high initial capacity and suppressing an increase in hysteresis during charging and discharging. It is also possible to provide an electric storage device including a plurality of such electric storage elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a perspective view of the electric storage element according to the present embodiment.

[0017] Figure 2 yes Figure 1 Cross-sectional view of the II-II line.

[0018] Figure 3 These are graphs showing examples of the physical properties of amorphous carbon as an active material for a negative electrode.

[0019] Figure 4 It is a perspective view of an electric storage device including the electric storage element according to the above-mentioned embodiment. DETAILED DESCRIPTION

[0020] Below, refer to Figure 1 as well as Figure 2 An embodiment of the storage element according to the present invention is described. The storage element includes a secondary battery, a capacitor, etc. In this embodiment, a secondary battery capable of charging and discharging is described as an example of a storage element. In addition, the names of the components (constituent elements) of this embodiment are the names in this embodiment, and sometimes they are different from the names of the components (constituent elements) in the background art.

[0021] The storage element 1 of the present embodiment is a non-aqueous electrolyte secondary battery. More specifically, the storage element 1 is a lithium ion secondary battery that utilizes the movement of electrons accompanying the movement of lithium ions. Such a storage element 1 supplies electric energy. The storage element 1 is used singly or in plurality. Specifically, the storage element 1 is used singly when the required output and the required voltage are small. On the other hand, the storage element 1 is combined with other storage elements 1 for use in a storage device when at least one of the required output and the required voltage is large. In the storage device, the storage element 1 used for the storage device supplies electric energy.

[0022] like Figure 1 as well as Figure 2 As shown, the storage element 1 includes: an electrode body 2 including a positive electrode and a negative electrode; a case 3 accommodating the electrode body 2; and an external terminal 7 disposed outside the case 3 and electrically connected to the electrode body 2. In addition to the electrode body 2, the case 3 and the external terminal 7, the storage element 1 also includes a current collecting member 5 that electrically connects the electrode body 2 and the external terminal 7.

[0023] The electrode body 2 is formed by winding a stacked body 22 in which positive electrodes and negative electrodes are stacked in a state of being insulated from each other by a separator.

[0024] The positive electrode comprises: a metal foil (current collector); and a positive electrode active material layer, which is overlapped on the surface of the metal foil and contains an active material. In this embodiment, the positive electrode active material layer is overlapped on both sides of the metal foil. In addition, the thickness of the positive electrode can be greater than 40 μm and less than 150 μm.

[0025] The metal foil is in a strip shape. The metal foil of the positive electrode of this embodiment is, for example, aluminum foil. The positive electrode has a non-covered portion of the positive electrode active material layer (a portion where the positive electrode active material layer is not formed) at one edge portion in the width direction which is the short side direction of the strip shape.

[0026] The positive electrode active material layer includes: a particulate active material (active material particles), a particulate conductive aid, and a binder. The thickness of the positive electrode active material layer (one layer) can be greater than 12 μm and less than 70 μm. The unit area weight of the positive electrode active material layer (one layer) can be 0.4 g / 100 cm 2 Above and 1.7g / 100cm 2 The density of the positive electrode active material layer can be 1.5 g / cm 3 Above and 3.0g / cm 3 The basis weight and density are the amounts in one layer arranged to cover one surface of the metal foil.

[0027] The weight per unit area of ​​the positive electrode active material layer can be calculated by the following method. When measuring the density of the battery being manufactured and used, the battery is discharged to 2.0V at a current of 3A (a current equivalent to 1C when the rated capacity of the battery can be known), and then maintained at 2.0V for 5 hours. After maintaining it for 5 hours, the electrode body is taken out from the inside of the shell in a dry room or an argon atmosphere glove box. The positive electrode taken out from the electrode body is washed more than 3 times with DMC (dimethyl carbonate) with a purity of more than 99.9% and a moisture content of less than 20ppm. Then, the DMC is removed by vacuum drying. Thereafter, the set area S (cm 2 ), for example 4cm 2 The test piece of size (2cm×2cm) is measured for weight W1 (mg). The active material layer and the metal foil are separated by immersion in pure water, etc. After separation, the weight of the metal foil is measured for W2 (mg). The weight per unit area of ​​the active material layer is calculated by (W1-W2) / S.

[0028] The average secondary particle diameter D50 of the active material particles in the positive electrode active material layer may be 2.0 μm or more and 20 μm or less. The average secondary particle diameter D50 is determined by a laser diffraction / scattering method.

[0029] The porosity of the positive electrode active material layer can be greater than 20% and less than 50%. The porosity can also be less than 45%. The porosity is measured by mercury intrusion. The mercury intrusion can be performed using a mercury intrusion instrument. Specifically, the mercury intrusion is performed based on Japanese Industrial Standards (JIS R1655: 2003). Regarding the porosity p (%), the mercury intrusion amount A (cm2) measured by the mercury intrusion method is used. 3 ), and the apparent volume V (cm 3 ), calculated by p = (A / V) × 100. Here, the apparent volume V (cm 3 ) refers to the area of ​​the active material layer when viewed from above (cm 2 ) multiplied by the thickness (cm) of the active material layer to obtain the volume. In addition, in the case of measuring the porosity of the positive electrode active material layer in the manufactured battery, for example, after the battery is discharged, the battery is disassembled in a dry atmosphere. Then, after the positive electrode active material layer is taken out and washed with dimethyl carbonate, it is vacuum dried for more than 2 hours. Then, the porosity of the positive electrode active material layer can be calculated based on the measurement results by using a mercury intrusion instrument.

[0030] The active material of the positive electrode is a compound that can absorb and release lithium ions. The active material of the positive electrode is, for example, a lithium transition metal oxide. Specifically, the active material of the positive electrode is, for example, LipMeO t(Me represents one or more transition metals) represented by a composite oxide (Li p Co s O2、Li p Ni q O2、Li p Mn r O4、Li p Ni q Co s Mn r O2, etc.), or, through Li p Me u (XO v ) w (Me represents one or more transition metals, and X represents, for example, P, Si, B, or V) represented by a polyanion compound (Li p Fe u PO4、Li p Mn u PO4、Li p Mn u SiO4、Li p Co u PO4F, etc.).

[0031] In this embodiment, the active material of the positive electrode has an α-NaFeO2 structure and is composed of Li 1+x M 1-x The lithium transition metal composite oxide represented by the chemical composition of O2 (herein, M is a transition metal, 0<x<0.3), more specifically, is composed of Li p Ni q Mn r Co s O t A lithium transition metal composite oxide represented by a chemical composition of (wherein 0<p≤1.3, q+r+s=1, 0≤q≤1, 0≤r≤1, 0≤s≤1, 1.7≤t≤2.3). In addition, preferably, 0<q<1, 0<r<1, 0<s<1.

[0032] As mentioned above, Li p Ni q Mn r Co s O t The lithium transition metal composite oxide represented by the chemical composition is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 3 / 5 Co 1 / 5 Mn 1 / 5 O2、LiNi 4 / 5 Co 1 / 10Mn 1 / 10 O2, etc.

[0033] In this embodiment, the charge capacity (charging current per unit area of ​​electrode: 0.5 mA / cm 2 ) is preferably 110 mAh / g or more and 230 mAh / g or less. In addition, the above-mentioned charging capacity is more preferably 150 mAh / g or more and 200 mAh / g or less, and further preferably 160 mAh / g or more and 180 mAh / g or less.

[0034] When the active material of the positive electrode is a lithium transition metal oxide of the above composition and the above charging capacity is within the above numerical range, in relation to the charge and discharge capacity of the carbon material (non-graphitizable carbon) used for the negative electrode, both relatively high weight energy density and durability can be achieved.

[0035] Examples of the binder used for the positive electrode active material layer include polyvinylidene fluoride (PVdF), copolymers of ethylene and vinyl alcohol, polymethyl methacrylate, polyethylene oxide, polypropylene oxide, polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, and styrene butadiene rubber (SBR). The binder of this embodiment is polyvinylidene fluoride.

[0036] The conductive agent of the positive electrode active material layer is a carbonaceous material containing 98 mass % or more of carbon. Examples of the carbonaceous material are Ketjen Black (registered trademark), acetylene black, graphite, etc. The positive electrode active material layer of this embodiment includes acetylene black as the conductive agent.

[0037] The negative electrode has: a metal foil (current collector), and a negative electrode active material layer formed on the metal foil. In the present embodiment, the negative electrode active material layers overlap on both sides of the metal foil. The metal foil is in a strip shape. The material of the metal foil is preferably aluminum or an aluminum alloy. In the present embodiment, the metal foil is an aluminum foil or an aluminum alloy foil, preferably an aluminum foil. An aluminum alloy refers to an alloy containing more than 90% by mass of aluminum. A conductive layer can be formed on the surface of the metal foil containing aluminum. Since the metal foil contains aluminum, the dissolution of the metal foil can be suppressed even when the storage element becomes an over-discharged state, and it can be considered that the resistance to over-discharge is exerted. The negative electrode has a non-covered portion of the negative electrode active material layer (a portion where the negative electrode active material layer is not formed) at one end edge in the width direction of the short side direction of the strip shape. The thickness of the negative electrode can be greater than 40μm and less than 150μm.

[0038] The thickness of the negative electrode active material layer (per layer) may be 10 μm or more and 100 μm or less. The weight per unit area of ​​the negative electrode active material layer (per layer) may be 0.2 g / 100 cm 2 Above and 1.0g / 100cm2 The density of the negative electrode active material layer (per layer) can be 0.5 g / cm 3 Above and 6.0g / cm 3 the following.

[0039] The weight per unit area of ​​the negative electrode active material layer is calculated in the same manner as the weight per unit area of ​​the positive electrode active material layer. In the portion where the positive electrode active material layer and the negative electrode active material layer are opposite to each other, when the weight per unit area of ​​the positive electrode active material layer is VP and the weight per unit area of ​​the negative electrode active material layer is VN, the following relationship (1) can be satisfied. According to such a structure, a storage element 1 having tolerance to overdischarge can be obtained. The weight per unit area is measured in the same manner as the above method.

[0040] 0.4≤VN / VP≤0.6Relationship (1)

[0041] The negative electrode active material layer includes: a particulate active material (active material particles) and a binder. The negative electrode active material layer is arranged to face the positive electrode via a separator. The width of the negative electrode active material layer is greater than that of the positive electrode active material layer.

[0042] The active material of the negative electrode can contribute to the electrode reaction of the charge reaction and the discharge reaction in the negative electrode. The active material of the negative electrode of this embodiment is amorphous carbon. More specifically, the active material of the negative electrode is non-graphitizable carbon.

[0043] Here, amorphous carbon refers to the average interplanar spacing d of (002) planes determined by wide-angle X-ray diffraction using CuKα rays as a radiation source in a discharge state. 002 The non-graphitizable carbon is amorphous carbon having an average interplanar spacing d of 0.340 nm or more and 0.390 nm or less. 002 The non-graphitizable carbon has a diameter of 0.360 nm or more and 0.390 nm or less.

[0044] The amorphous carbon of the active material of the negative electrode has the following physical properties. Based on the result of measuring (measured during discharge) the potential (V) of the amorphous carbon relative to the discharge power (Q) of the amorphous carbon, the change ratio (dQ / dV) of the potential (V) under the discharge power (Q) of the amorphous carbon per unit amount is obtained, and the curve representing the change ratio (dQ / dV) relative to the potential (V) has one or more peaks in the range where the potential of the amorphous carbon is above 0.8V and below 1.5V. The height of the peak is preferably above 300mAh / g·V. The height of the peak is above 300mAh / g·V, so that a storage element 1 with a higher initial capacity can be obtained. The height of the peak can also be below 1500mAh / g·V. The above curve usually has a peak. The above curve is obtained according to the method described in the embodiment. In addition, the peak value of the above curve can be confirmed by visually observing the entire curve, and can also be confirmed as follows. In the curve graph representing the above curve, the discharge amount for every 0.1V change in potential (V) is calculated, and the average value of the change ratio (dQ / dV) is calculated. When the calculated average value of the change ratio (dQ / dV) temporarily rises and then falls when the potential of amorphous carbon is in the range of 0.8V to 1.5V, it can be confirmed that the above curve has a peak.

[0045] Amorphous carbon having the above-mentioned physical properties can be obtained by setting the firing temperature during manufacturing to 1000°C or less. By setting the firing temperature to 900°C or less, the peak value becomes larger. In this way, the amorphous carbon of the present embodiment is produced by firing at a relatively low temperature. On the other hand, conventional general amorphous carbon is produced at a firing temperature of 1300°C or more.

[0046] The binder used for the negative electrode active material layer is the same as the binder used for the positive electrode active material layer. The binder in this embodiment is styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC).

[0047] In the negative electrode active material layer, the ratio of the binder may be 0.5 mass % or more and 10 mass % or less relative to the total mass of the active material particles and the binder.

[0048] The negative electrode active material layer may further contain a conductive auxiliary agent such as Ketjen Black (registered trademark), acetylene black, graphite, etc. The negative electrode active material layer of this embodiment does not contain a conductive auxiliary agent.

[0049] When charging to the upper limit voltage (fully charged), the potential of the positive electrode can be above 3.85V and below 4.5V [vs.Li + / Li]. On the other hand, when charged to the upper limit voltage (fully charged), the potential of the negative electrode is 0.25V or more. When charged to the upper limit voltage (fully charged), the potential of the negative electrode can also be 0.35V or more and 0.4V or less [vs.Li + / Li]. The potential of the negative electrode when charged to the upper limit voltage (fully charged) is above 0.25V, so that it can have a relatively high initial capacity. In addition, the potential is above 0.25V, so that the alloying reaction between lithium and aluminum of the collector can be suppressed, so aluminum can be selected for the collector of the negative electrode, so that the storage element 1 with excellent over-discharge characteristics can be obtained. The potential of the negative electrode when charged to the upper limit voltage (fully charged) is below 0.4V, so that the capacity of the battery can be further increased. In addition, the potential of the negative electrode when charged to the upper limit voltage (fully charged) can be adjusted by changing the ratio of the unit area weight of the active material layer of the positive electrode and the negative electrode. For example, the potential of the above-mentioned negative electrode can be set high by increasing the value of the above-mentioned VN / VP.

[0050] The upper limit of the normal operating voltage of the following storage element 1 is 3.6 V. The storage element 1 includes a positive electrode having an α-NaFeO2 structure and Li 1+x M 1-x The invention discloses a lithium transition metal composite oxide represented by a chemical composition of 1,000 Nm (where M is a transition metal, 0 < x < 0.3), and is designed so that the voltage of the negative electrode becomes 0.25 V or more when the voltage of the storage element 1 reaches 3.6 V. When a plurality of such storage elements 1 are connected in series, preferably 4 are connected in series, the voltage is interchangeable with the power supply for automobiles equipped with lead storage batteries in the past, so it can be used as a substitute for lead storage batteries. If such a storage device is used as a substitute for lead storage batteries, deep discharge that cannot be performed in lead storage batteries can be achieved, and in addition, lightweighting can be achieved.

[0051] In the electrode body 2 of the present embodiment, the positive electrode and the negative electrode constructed as above are wound in a state of being insulated by the separator. That is, in the electrode body 2 of the present embodiment, the positive electrode, the negative electrode, and the stack 22 of the separator are wound. The separator is an insulating member. The separator is arranged between the positive electrode and the negative electrode. Thus, in the electrode body 2 (more specifically, the stack 22), the positive electrode and the negative electrode are insulated from each other. In addition, the separator retains the electrolyte in the housing 3. Thus, during the charge and discharge of the storage element 1, lithium ions move between the positive electrode and the negative electrode alternately stacked with the separator sandwiched therebetween.

[0052] The separator is in a strip shape. The separator has a porous separator substrate. The separator is arranged between the positive electrode and the negative electrode to prevent a short circuit between the positive electrode and the negative electrode. The separator of this embodiment has only a separator substrate.

[0053] The separator substrate is porous. The separator substrate is, for example, a woven fabric, a nonwoven fabric, or a porous film. As the material of the separator substrate, polymer compounds, glass, ceramics, etc. can be cited. As the polymer compound, for example, at least one selected from the group consisting of polyesters such as polyacrylonitrile (PAN), polyamide (PA), polyethylene terephthalate (PET), polyolefins (PO) such as polypropylene (PP), polyethylene (PE), and cellulose can be cited.

[0054] The width of the separator (the dimension of the short side of the strip shape) is slightly larger than the width of the negative electrode active material layer. The separator is arranged between the positive electrode and the negative electrode that are overlapped in a manner that the positive electrode active material layer and the negative electrode active material layer are overlapped and in a state where the positions are offset in the width direction. At this time, the non-covered portion of the positive electrode and the non-covered portion of the negative electrode do not overlap. That is, the non-covered portion of the positive electrode protrudes in the width direction from the area where the positive electrode and the negative electrode overlap, and the non-covered portion of the negative electrode protrudes in the width direction (in the direction opposite to the protruding direction of the non-covered portion of the positive electrode) from the area where the positive electrode and the negative electrode overlap. The electrode body 2 is formed by winding the stacked positive electrode, the negative electrode, and the separator, that is, the stack 22.

[0055] The shell 3 includes: a shell body 31 having an opening; and a cover plate 32 that blocks (closes) the opening of the shell body 31. The shell 3 contains the electrolyte together with the electrode body 2 and the current collecting member 5 in the internal space. The shell 3 is formed of a metal that is resistant to the electrolyte. The shell 3 is formed of an aluminum-based metal material such as aluminum or an aluminum alloy. The shell 3 can also be formed of a metal material such as stainless steel and nickel, or a composite material in which a resin such as nylon is bonded to aluminum.

[0056] The electrolyte is a non-aqueous electrolyte. The electrolyte is obtained by dissolving an electrolyte salt in an organic solvent. Examples of organic solvents include cyclic carbonates such as propylene carbonate and ethylene carbonate, and chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The electrolyte salts are LiClO4, LiBF4, and LiPF6. The electrolyte of the present embodiment is an electrolyte obtained by dissolving 0.5 to 1.5 mol / L of LiPF6 in a mixed solvent in which propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are mixed in a given ratio.

[0057] The cover plate 32 has a gas discharge valve 321 capable of discharging gas in the housing 3 to the outside. The gas discharge valve 321 discharges gas from the housing 3 to the outside when the internal pressure of the housing 3 rises to a predetermined pressure. The gas discharge valve 321 is provided at the center of the cover plate 32.

[0058] The housing 3 is provided with an injection hole for injecting electrolyte. The injection hole connects the inside and outside of the housing 3. The injection hole is provided on the cover plate 32. The injection hole is sealed (blocked) by an injection plug 326. The injection plug 326 is fixed to the housing 3 (the cover plate 32 in the example of the present embodiment) by welding.

[0059] The external terminal 7 is a portion electrically connected to the external terminal 7 of another power storage element 1 or an external device. The external terminal 7 is formed of a conductive member. The external terminal 7 has a surface 71 to which a bus bar or the like can be welded. The surface 71 is a flat surface.

[0060] The current collecting member 5 is disposed in the housing 3 and is directly or indirectly connected to the electrode body 2 so as to be electrically conductive. The current collecting member 5 of this embodiment is formed of a conductive member. Figure 2 As shown, the current collecting member 5 is arranged along the inner surface of the case 3. The current collecting member 5 is electrically connected to the positive electrode and the negative electrode of the energy storage element 1, respectively.

[0061] In the electric storage device 1 of the present embodiment, the electrode body 2 (more specifically, the electrode body 2 and the current collecting member 5 ) is housed in the case 3 in a state of being housed in a bag-shaped insulating cover 6 that insulates the electrode body 2 and the case 3 .

[0062] Next, a method for manufacturing the electric storage device 1 according to the above-described embodiment will be described.

[0063] In the method for manufacturing the storage element 1, first, a mixture containing an active material is applied to a metal foil (collector) to form an active material layer to produce electrodes (positive electrode and negative electrode). Then, the positive electrode, separator, and negative electrode are stacked to form an electrode body 2. Next, the electrode body 2 is placed in a case 3, and an electrolyte is placed in the case 3 to assemble the storage element 1.

[0064] In the production of an electrode (positive electrode), a mixture containing an active material, a binder and a solvent is applied to both sides of a metal foil to form a positive electrode active material layer. By changing the amount of the mixture applied, the thickness and unit area weight of the positive electrode active material layer can be adjusted. As a coating method for forming a positive electrode active material layer, a general method can be adopted. Furthermore, the positive electrode active material layer is rolled at a given pressure. By changing the pressing pressure, the thickness and density of the positive electrode active material layer can be adjusted. In addition, a negative electrode is made in the same manner.

[0065] In forming the electrode body 2, a stacked body 22 with a separator sandwiched between the positive electrode and the negative electrode is wound to form the electrode body 2. Specifically, the positive electrode, the separator, and the negative electrode are stacked so that the positive electrode active material layer and the negative electrode active material layer face each other with the separator interposed therebetween to form the stacked body 22. The stacked body 22 is wound to form the electrode body 2.

[0066] In assembling the electric storage element 1, the electrode body 2 is placed in the case body 31 of the case 3, the opening of the case body 31 is blocked with the cover plate 32, and the electrolyte is injected into the case 3. When the opening of the case body 31 is blocked with the cover plate 32, the electrode body 2 is placed in the case body 31, and the opening of the case body 31 is blocked with the cover plate 32 in a state where the positive electrode and one external terminal 7 are connected, and the negative electrode and the other external terminal 7 are connected. When injecting the electrolyte into the case 3, the electrolyte is injected into the case 3 from the injection hole of the cover plate 32 of the case 3.

[0067] The energy storage device 1 of the present embodiment configured as described above is generally used so that the potential of the negative electrode does not reach the alloying potential of aluminum and lithium because the metal foil of the negative electrode is aluminum.

[0068] The storage element 1 of the present embodiment constructed as described above includes a negative electrode having a negative electrode active material layer containing amorphous carbon as an active material. Based on the result of measuring the potential (V) of amorphous carbon relative to the discharge quantity (Q) of amorphous carbon, the change ratio (dQ / dV) of the potential (V) per unit amount of the discharge quantity (Q) of amorphous carbon is obtained, and a curve representing the change ratio (dQ / dV) relative to the potential (V) has one or more peaks in the range where the potential of amorphous carbon is 0.8V or more and 1.5V or less. The potential of the negative electrode when the storage element 1 is fully charged is 0.25V or more according to the lithium potential.

[0069] The amorphous carbon having the above-mentioned physical properties is composed of a pore structure different from that of conventional amorphous carbon, and therefore has the above-mentioned peak value. The amount of charge corresponding to the amount of the amorphous carbon having the above-mentioned peak value increases, and it is presumed that the storage element 1 can obtain a larger capacity. In addition, the potential of the negative electrode when fully charged is 0.25 V or more according to the lithium potential, so it is considered that the increase in the hysteresis of the storage element 1 during charging and discharging is suppressed.

[0070] Therefore, according to the above configuration, it is possible to provide an electric storage element having a relatively high initial capacity and suppressing an increase in hysteresis during charging and discharging. In addition, in the electric storage element 1 in which an increase in hysteresis is suppressed, it becomes relatively easy to control charging and discharging.

[0071] In addition, the storage element of the present invention is not limited to the above-mentioned embodiment, and it is self-evident that various changes can be made within the scope of the present invention. For example, the structure of another embodiment can be added to the structure of a certain embodiment, and a part of the structure of a certain embodiment can be replaced with the structure of another embodiment. Furthermore, a part of the structure of a certain embodiment can be deleted.

[0072] In the above-mentioned embodiment, the positive electrode and the negative electrode in which the active material layer containing the active material is directly connected to the metal foil are described in detail, but in the present invention, the positive electrode or the negative electrode may have a conductive layer containing a binder and a conductive auxiliary agent, and the conductive layer is arranged between the active material layer and the metal foil. That is, the metal foil of the positive electrode or the negative electrode may overlap with the active material layer via the conductive layer.

[0073] In the above embodiment, the active material layers are arranged on both sides of the metal foil of each electrode. However, in the electric storage device of the present invention, the positive electrode or the negative electrode may include an active material layer only on one side of the metal foil.

[0074] In the above embodiment, the storage element 1 having the electrode body 2 formed by winding the laminated body 22 is described in detail, but the storage element of the present invention may also have an unwound laminated body 22. In detail, the storage element may also have an electrode body in which a positive electrode, a separator, a negative electrode, and a separator each formed in a rectangular shape are stacked multiple times in this order.

[0075] In the above embodiment, the case where the storage element 1 is used as a non-aqueous electrolyte secondary battery (such as a lithium ion secondary battery) capable of charge and discharge is described, but the type and size (capacity) of the storage element 1 are arbitrary. In addition, in the above embodiment, a lithium ion secondary battery is described as an example of the storage element 1, but it is not limited to this. For example, in addition to being applicable to various secondary batteries, the present invention can also be applied to storage elements of capacitors such as double-layer capacitors.

[0076] The storage element 1 (e.g., a battery) can also be used in Figure 4 The power storage device 100 shown (a battery module when the power storage element is a battery) includes: at least two (a plurality of, for example, four) power storage elements 1; and a bus bar member 91 that electrically connects two adjacent power storage elements 1 to each other. The plurality of power storage elements 1 are preferably connected in series. The technology of the present invention can be applied to a part of the plurality of power storage elements, or to all of the plurality of power storage elements.

[0077] <Mechanism of Suppressing Increase in Hysteresis>

[0078] In the negative electrode active material (amorphous carbon), there are multiple sites where Li ions can be inserted, and the energy level (zero-point energy) of each site is different. During charging, first, Li ions are inserted into sites with low energy levels, and the potential energy of the site increases (transition). Then, at the time point when the potential energy curve (energy level) intersects with other sites, (because the result is that the energy level of other sites becomes lower) Li ions move to other sites. In addition, according to energy stabilization, internal energy is released as energy to the outside. During discharge, the opposite phenomenon occurs. The inter-site movement of Li ions that depends on the energy level difference in the negative electrode active material during charging and discharging becomes the cause of hysteresis during charging and discharging.

[0079] In other words, if the inter-site movement of Li ions is restricted, hysteresis will not occur. Therefore, if it is possible to charge and discharge under conditions of shallow depth of charge so that the energy level does not cross, it can be considered that no hysteresis occurs. The amorphous carbon involved in the present invention has one or more peaks in a range where the potential (V) is above 0.8V and below 1.5V in a curve representing the change ratio (dQ / dV) of the discharge power per unit amount relative to the potential (V), so that the potential of the negative electrode when fully charged is set to 0.25V or more relative to the metal lithium potential, so that even if the energy level does not cross under conditions of shallow depth of charge, it also has a relatively high initial capacity.

[0080] Furthermore, by adjusting the sintering temperature, amorphous carbon under desired conditions can be produced.

[0081] Example

[0082] As shown below, a nonaqueous electrolyte secondary battery (lithium ion secondary battery) was manufactured.

[0083] (Example 1)

[0084] (1) Preparation of positive electrode

[0085] N-methyl-2-pyrrolidone (NMP) as a solvent was mixed with a conductive additive (acetylene black), a binder (PVdF), an active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The particles of O2, D50 of 4.0 μm) were mixed and blended to prepare a positive electrode mixture. The amounts of conductive aid, binder, and active material were set to 4.5 mass%, 2.5 mass%, and 93 mass%, respectively. The prepared positive electrode mixture was applied to both sides of aluminum foil (thickness 12 μm) so that the coating amount (weight per unit area) after drying was 0.613 g / 100 cm 2 The coating amount was set so that the potential of the positive electrode when the battery was charged to the upper limit voltage of the battery as shown in Table 1 was 4.00 V [vs. Li + / Li]. After drying, rolling was performed. Then, vacuum drying was performed to remove moisture, etc. The thickness of the active material layer (one layer) after pressing was 64 μm. The porosity of the active material layer was 42%.

[0086] (2) Preparation of negative electrode

[0087] As an active material, particulate amorphous carbon (difficult to graphitize carbon) (described in detail later) was used. In addition, PVdF was used as a binder. NMP as a solvent was mixed with the binder and the active material and mixed evenly to prepare a mixture for the negative electrode. If converted to solid content, PVdF was prepared to be 4% by mass and the active material was prepared to be 96% by mass. The prepared mixture for the negative electrode was applied to both sides of an aluminum foil (thickness 12 μm) so that the coating amount (weight per unit area) after drying became 0.3 g / 100 cm 2 The coating amount was set so that the potential of the negative electrode when the battery was charged to the upper limit voltage of the battery as shown in Table 1 would be 0.40 V [vs. Li + / Li]. After drying, the mixture was rolled and vacuum dried to remove moisture, etc. The thickness of the active material layer (one layer) was 71 μm. The porosity of the active material layer was 32%.

[0088] (3) Isolation parts

[0089] As the separator, a polyethylene microporous film having a thickness of 22 μm was used. The polyethylene microporous film had an air permeability barrier of 100 sec / 100 cc.

[0090] (4) Preparation of electrolyte

[0091] As the electrolyte, an electrolyte prepared by the following method was used: as a non-aqueous solvent, a solvent prepared by mixing 1 volume part of each of propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate was used, and LiPF6 was dissolved in the non-aqueous solvent so that the salt concentration became 1 mol / L to prepare an electrolyte.

[0092] (5) Arrange the electrode body in the shell

[0093] A battery was manufactured by a common method using the above-mentioned positive electrode, the above-mentioned negative electrode, the above-mentioned electrolyte, the separator, and the case.

[0094] First, the separator is arranged between the positive electrode and the negative electrode, and the sheet is wound. Then, the wound electrode body is arranged in the shell body of the square aluminum battery tank as the shell. Next, the positive electrode and the negative electrode are electrically connected to the two external terminals respectively. Then, the cover plate is installed on the shell body. The above-mentioned electrolyte is injected into the shell from the injection port formed on the cover plate of the shell. Finally, the shell is sealed by sealing the injection port of the shell.

[0095] (Examples 2 to 5, Comparative Examples 1 to 3)

[0096] By changing the type of amorphous carbon as the active material of the negative electrode, or by 2 Lithium ion secondary batteries were manufactured in the same manner as in Example 1 except that the weight per unit area when producing the negative electrode was changed within a range of , thereby changing each battery to the structure shown in Table 1. The negative electrode potential of the lithium ion secondary battery designed to the upper limit voltage became the value shown in Table 1.

[0097] In detail, in Examples 2 to 4, the same amorphous carbon (Sample 1) as in Example 1 was used as the active material of the negative electrode. In Example 5, amorphous carbon (Sample 2 which is different from Sample 1) having one peak in the curve representing the change ratio (dQ / dV) with respect to the potential (V) was used as the active material of the negative electrode. In addition, in the amorphous carbon of Samples 1 and 2, the height of the peak was 300 mAh / g·V or more.

[0098] In Comparative Examples 2 and 3, amorphous carbon having no peak in the curve showing the change ratio (dQ / dV) with respect to potential (V) was used as the negative electrode active material. In Comparative Example 1, amorphous carbon of Sample 1 described above was used as the negative electrode active material.

[0099] The curves showing the change ratio (dQ / dV) with respect to the potential (V) for the above-mentioned sample 1, the above-mentioned sample 2, and the amorphous carbon without a peak are shown in FIG. Figure 3 Sample 1 is a sample obtained by firing at 900° C., and Sample 2 is a sample obtained by firing at 1000° C. Amorphous carbon having no peak is amorphous carbon obtained by firing at 1300° C.

[0100] Figure 3The curve shown is a curve that calculates the change ratio (dQ / dV) of the potential (V) per unit amount of discharge charge (Q) based on the result of measuring the potential (V) of amorphous carbon relative to the discharge charge (Q) of amorphous carbon, and represents the change ratio (dQ / dV) relative to the potential (V). The above curve is obtained by measuring the charge of amorphous carbon during discharge. In this measurement method, after a given pretreatment is performed on amorphous carbon, the charge relative to the potential during discharge is measured.

[0101] (Pre-processing)

[0102] After the battery was discharged to 2.0V at a current of 5A, it was kept at 2.0V for 5 hours. After being kept, it was paused for 5 hours, and the electrode body was taken out from the inside of the shell in a dry room or a glove box with argon atmosphere. The negative electrode taken out from the electrode body was washed more than 3 times with DMC having a purity of 99.9% or more and a moisture content of 20ppm or less. Then, the DMC was removed by vacuum drying.

[0103] (Method for measuring the amount of electricity during discharge)

[0104] As described above, after removing the negative electrode from the battery through pretreatment, a three-pole single cell was prepared, which had a negative electrode (working electrode) cut into 3.0 cm × 2.5 cm, a counter electrode (Li metal), and a reference electrode (Li metal). As a separator and an electrolyte, the same separator and electrolyte as those described in Example 1 were used. The prepared single cell was charged at a current density of 0.5 mA / cm 2 The battery is charged at a constant voltage for 24 hours to 0.01V at a current value of 1CmA. After a 10-minute pause, constant current discharge is performed at the same current density to 2.0V. The calculated value of the discharge capacity under such operation is set to 1CmA. Using the same single battery, the operation of constant current charging at a current value of 1CmA for 36 seconds and then pausing for 720 seconds is performed 99 times, and then constant voltage charging is performed at the same current value and 0.01V for 30 minutes. Next, after a 720-second pause, constant current discharge is performed at the same current value with a lower limit voltage of 2.0V for 36 seconds, and then paused for 720 seconds. This operation is performed 100 times. The value (change ratio) obtained by dividing the difference between the potentials after the pause of adjacent discharges in the measurement sequence by the difference in the discharge quantities corresponding to each potential is set to dQ / dV. The curve showing the change ratio (dQ / dV) with respect to each potential (V) after the discharge pause has one peak in the amorphous carbon of Samples 1 and 2 within the range where the potential of the amorphous carbon is 0.8 V or more and 1.5 V or less.

[0105] <Determination of Initial Capacity>

[0106] After charging at 3A constant current to 3.6V at 25°C, constant voltage charging was performed at 3.6V, and constant current charging and constant voltage charging were performed for a total of 3 hours. Then, the battery was discharged at a constant current of 3A to 2.4V. This discharge capacity was defined as the "initial capacity".

[0107] <Measurement of hysteresis during charging and discharging>

[0108] The hysteresis is calculated under the following conditions. The initial capacity calculated above is set to 1CA. After discharging at a constant current of 3A and a termination voltage of 2.4V, charging at 1CA for 36 seconds and then pausing for 720 seconds is set as 1 time. This charging is repeated 99 times. Constant voltage charging at 1.5A for 3600 seconds at 3.6V is performed. Then, discharging at 1CA for 36 seconds and then pausing for 720 seconds is set as 1 time. This discharge is repeated 100 times. The voltage after each pause during charging is set as the OCV during charging, and the voltage after each pause during discharging is set as the OCV during discharging. The calculation is performed relative to each SOC. At each SOC, the difference between the OCV during charging and the OCV during discharging is set as the hysteresis.

[0109] Table 1 shows the measurement results of the initial capacity of the batteries manufactured in each example and each comparative example, and the evaluation results of the hysteresis during charge and discharge.

[0110] [Table 1]

[0111]

[0112] As can be understood from Table 1, the battery of the example has a relatively high initial capacity and the increase of hysteresis during charging and discharging is suppressed.

[0113] Explanation of symbols

[0114] 1: Storage element (non-aqueous electrolyte secondary battery);

[0115] 2: Electrode body;

[0116] 3: housing; 31: housing body; 32: cover plate;

[0117] 5: Current collecting components;

[0118] 6: Insulation cover;

[0119] 7: External terminal; 71: Surface;

[0120] 100: Power storage device.

Claims

1. A storage element comprising a negative electrode, the negative electrode having a negative electrode active material layer, the negative electrode active material layer containing amorphous carbon obtained by calcining at 1000° C. or less as an active material, The unit area weight of the negative electrode active material layer is 0.2 g / 100 cm 2 Above and 1.0g / 100cm 2 the following, Based on the result of measuring the potential V of the amorphous carbon relative to the discharge quantity Q of the amorphous carbon, a change ratio dQ / dV of the potential V per unit amount of the discharge quantity Q is obtained, and a curve representing the change ratio dQ / dV relative to the potential V has one or more peaks in the range of the potential of the amorphous carbon being greater than or equal to 0.8 V and less than or equal to 1.5 V, The potential of the negative electrode when fully charged is 0.25 V or more in terms of lithium potential.

2. The electric storage element according to claim 1, wherein The potential of the negative electrode when fully charged is 0.35 V or more in terms of lithium potential.

3. The electric storage element according to claim 1 or 2, wherein: The height of the peak is 300 mAh / g·V or more.

4. The electric storage element according to claim 1 or 2, wherein: The negative electrode has a metal foil containing aluminum.

5. A power storage device comprising a plurality of power storage elements according to any one of claims 1 to 4, A plurality of the power storage elements are connected in series, The storage element has a positive electrode, which contains a lithium transition metal composite oxide as an active material. The lithium transition metal composite oxide has an α-NaFeO2 structure and is composed of Li 1+x M 1-x The chemical composition of O2 is expressed as follows: M is a transition metal, 0 <x<0.3。 6. A storage element comprising a negative electrode, the negative electrode having a negative electrode active material layer, the negative electrode active material layer containing amorphous carbon obtained by calcining at 1000° C. or less as an active material, The unit area weight of the negative electrode active material layer is 0.2 g / 100 cm 2 Above and 1.0g / 100cm 2 the following, Based on the result of measuring the potential V of the amorphous carbon relative to the discharged quantity Q1 of the amorphous carbon, a curve representing the change ratio dQ1 / dV of the discharged quantity Q1 per unit amount relative to the potential V has one or more peaks in the range where the potential V is greater than or equal to 0.8 V and less than or equal to 1.5 V, The potential of the negative electrode when fully charged is 0.25 V or more relative to the potential of metal lithium.

Citation Information

Patent Citations

  • Lithium ion secondary battery

    JP2016091927A

  • Nonaqueous electrolyte secondary battery and method for production of nonaqueous electrolyte secondary battery

    CN103531842A